Comparison of Peripheral Biomarkers and Reduction of Stress Response in Patients With Major Depressive Disorders vs. Panic Disorder - Park, Mi Jin; Jang, Eun Hye; Kim, Ah Young; Kim, Hyewon; Kim, Hyun Soo; Byun, Sangwon; Yu, Han Young; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
Alteration in stress response seems to affect the development of psychiatric disorders. In this study, we aimed to investigate whether baseline peripheral biomarkers could predict the reduction of stress response among patients with major depressive disorder (MDD) and panic disorder (PD). Patients with MDD (n = 41), PD (n = 52), and healthy controls (HC, n = 59) were selected and regularly followed up with five visits during 12 weeks. The severity of stress at every visit was assessed using Stress Response Inventory (SRI) and peripheral biomarkers were measured by blood tests at baseline, 2 weeks, 4 weeks, 8 weeks, and 12 weeks. Interleukin (IL)-6, IL-10, Tumor necrosis factor (TNF)-α, Interferon (IFN)-γ, C-reactive protein (CRP), adiponectin, and leptin levels were analyzed using enzyme-linked immunosorbent assays. Reduction of stress response was defined as the difference in SRI score between baseline and 12 weeks divided by the baseline score. SRI scores were significantly (p < 0.0001) higher in patients with MDD and PD than in HC at every visit after adjusting for variables. In multivariable linear regression, adiponectin levels at baseline were significantly associated with reduction of stress response in patients with PD. When adiponectin increased 1 mg/l, stress response decreased 0.781 points (β = -0.781, S.E. = 0.220, p = 0.001). Among subscales of SRI, somatization had a moderate negative correlation with adiponectin levels (r = -0.469). There was no significant association between baseline peripheral biomarkers and reduction of stress response in patients with MDD. Our study showed an inverse association between baseline adiponectin levels and stress response changes in patients with PD, but not in patients with MDD. Thus, differentiated approaches for assessing and treating stress responses of patients with PD and MDD might be helpful. Larger and longitudinal studies are necessary to establish the role and action of mechanism of adiponectin in regulating stress responses in PD.